"A DISMAL BUT PROFITABLE DITCH": THE SUEZ CANAL THEN AND NOW. Issue 1 (2nd January 2016) - Searight, Sarah
Abstract : This article traces the history of the Suez Canal since its origins in the 19 th century to the present-day. It gives an outline not only of the antecedents of the Canal, but also looks at the August 2015 widening and deepening of the Canal with its effects of the Egyptian economy and international commerce.